Islamic Perspective of Knowledge Management - Aini, Ahmad (Edward Elgar Publishing, 2014)
Since the idea of knowledge management is widespread all over the globe, it is timely to discuss the idea in a different context. A discussion of knowledge management in a religious context is still not established. This chapter discusses the idea of knowledge management in the Islamic context. It examines the Islamic view on knowledge, the idea of knowledge management in general and explores the seven C’s knowledge management framework against Islamic principles.